Intensive working memory training: A single case experimental design in a patient following hypoxic brain damage. (December 2014) - Hynes, S. M.; Fish, J.; Manly, T.
Abstract Background: Recent reports suggest that intensive, progressive training on working memory tasks can lead to generalized cognitive gains. Case study: A patient, following hypoxic brain damage, showed significant difficulties in working memory and time-perception. This study examined the impact and specificity of any benefits resulting from automated working memory training (AWMT) in comparison with the effects of an equivalent programme that emphasized automated novel problem-solving (APST) which served as an active control. Following initial assessment, the patient trained for 4 weeks (20 days), 20–30 minutes a day on the APST tasks before repeating key outcome measures. He then trained for an identical period on AWMT. Results: There were no cognitive gains apparent following APST. Furthermore, there were no disproportionate gains on digit span following AWMT. AWMT was, however, associated with improvement in time-perception that had previously been resistant to rehabilitation. In line with previous reports, AWMT was also followed by gains on a measure of planning. Conclusion: The results provide encouraging evidence that AWMT may have generalized benefits in the context of impaired WM capacity following brain injury.